FAKTOR – FAKTOR YANG MEMPENGARUHI HARGA SAHAM PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - srisucisetyani; Bahtiar Usman (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to analyze the factors that affect stock prices in mining companies listed on the Indonesia Stock Exchange (IDX) for the 2015-2020 period, namely Liquidity, Exchange Rate, FDI, ROA, Company Size and Leverage factors. The method used in this study is a quantitative research approach with a sample of 19 coal mining sector companies listed on the IDX and issuing audited financial reports for the 2015-2020 period. Data testing is done by selecting the panel data model through the Chow test, Hausman test, and the Lagrange multiplier test with the conclusion using the Random Effects model. The data analysis used to test the hypothesis is multiple regression analysis using the Eviews 10 software program. The results show that Liquidity and Leverage partially have an influence on the stock prices of mining sector companies listed on the IDX. However, the Exchange Rate, FDI, ROA and Company Size partially have no effect on the stock price of mining sector companies listed on the IDX. The results of this study provide information for companies and investors to consider Liquidity and Leverage in investment analysis or take company policies because they affect stock prices.